USING INNOVATIVE TECHNOLOGIES IN TEACHING MATERIALS SCIENCE - Mamadaliyeva Husnida Odiljonovna (PEDAGOGS, 2024)
Annotation:  This article explores the integration of innovative technologies in the teaching of materials science, focusing on enhancing the educational process through advanced tools and methodologies. The study highlights the role of digital platforms, simulations, and virtual laboratories in improving students' comprehension of complex concepts. Key innovations discussed include the use of augmented and virtual reality for interactive learning, AI-driven adaptive systems for personalized education, and data-driven tools for analyzing material properties. By incorporating these technologies, educators can foster deeper understanding, engage students effectively, and better prepare them for modern industrial challenges. The findings underscore the importance of aligning teaching strategies with technological advancements to meet the demands of 21st-century education.